Legal Consequentials: an Information Seeking Task. (December 2022) - Gregory, Stephen
Abstract: This article is a summary of a parallel session delivered by Stephen Gregory at the BIALL Conference 2022. We may frequently work with amended legislation but have we ever stopped to think about the processes involved in identifying and implementing amendments? Drawing on experiences of working with government lawyers this article explores how government legal information professionals can assist in identifying candidates for consequential amendment. The complexities of searching for references to specific legislation provisions are described, providing some suggested search solutions. A risk-based approach is suggested. He concludes that by working collaboratively government information professionals may add significant value and benefit.